Adhesive modified ionic conductive hydrogel capable of being used for temperature and humidity sensing, preparation method of adhesive modified ionic conductive hydrogel and storage equipment
By using the covalent-physical composite crosslinking structure in ionic conductive hydrogels, the problems of insufficient adhesion, limited drying resistance and insufficient freezing resistance are solved, and higher mechanical properties and more stable properties are achieved in dry and low temperature environments.
Patent Information
- Application Number
- CN202411992234.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-21
AI Technical Summary
The existing ionic conductive hydrogels have insufficient adhesion in practical applications, making them difficult to maintain stable performance in dry environments, and are prone to freezing in low-temperature environments, affecting their mechanical properties and conductive sensitivity.
The step-by-step introduction method of in-situ + non-in-situ exchange of solvent phase and conductive phase is adopted to improve the adhesion, drying and frost resistance of the hydrogel through the formation of covalent-physical composite crosslinking structures, and is used for the assembly of resistive flexible stress strain, temperature and humidity sensors.
It significantly improves the adhesion and mechanical properties of the hydrogel, enhances its stability in dry and low temperature environments, and can be effectively used in versatile sensor applications.
Smart Images

Figure CN119661963A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of material technology, and in particular to an adhesion-modified composite ion conductive hydrogel capable of being used for temperature and humidity sensing, and a preparation method and storage device thereof. Background Art
[0002] As a water-rich three-dimensional structural elastomer, the conductivity of hydrogel is closely related to the internal doping of the conductive phase material therein, and can be mainly divided into electronic conductive hydrogel and ion conductive hydrogel. For electronic conductive hydrogel, the conductive polymer network and conductive nanomaterials introduced into the matrix usually have large differences in mechanical properties from the hydrogel matrix. It cannot withstand large strains during deformation like the matrix network, which often leads to irreversible separation of the connected conductive polymer network or bridging nanomaterials from the matrix, causing irreversible transformation of electrical properties. For ion conductive hydrogel, its conductive pathway is mainly the internal water pathway, and the change in ion movement distance caused by hydrogel deformation is converted into a change in conductivity, which is not affected by the above problems during electronic conduction, making ion conductive hydrogel have specific advantages due to its biomimetic mechanical properties and unique ion conduction behavior.
[0003] The study obtained good mechanical properties, electrical conductivity, and response and sensing capabilities of stress-strain, temperature, and humidity signals by constructing and regulating the solution of ion-conductive hydrogel. However, the surface of the series of hydrogels prepared by them is smooth and does not have adhesion. When they are actually assembled into flexible sensor devices, they need additional auxiliary fixation. In addition, the performance of hydrogels needs to be stable during the application process in a wide temperature range, not only under dry conditions, but also hydrogels with high water content are prone to freezing in low temperature environments, which will also have a great impact on their mechanical properties and conductive sensitivity.
[0004] In the process of storing adhesive modified ion conductive hydrogels for temperature and humidity sensing, the existing technology has the following major deficiencies: Insufficient adhesion: Many ion-conductive hydrogels have smooth surfaces and lack adhesion, which requires additional auxiliary fixation in practical applications, increasing the complexity and cost of use. For example, in the Journal of Analytical Chemistry (FENXI HUAXUE) Review and Progress, the article "Conductive Hydrogels and Their Applications in Flexible Electronic Devices" mentioned that although adhesion can be enhanced by introducing functional groups such as catechol, amino, hydroxyl or carboxyl, these methods require complex chemical treatments in actual production. Secondly, hydrogels are prone to water loss under dry conditions, resulting in loss of flexibility and function, which limits their application in dry environments. For example, untreated PVA hydrogels lose almost all their water in a dry environment. In addition, hydrogels are prone to freezing in low-temperature environments, affecting their mechanical properties and conductive sensitivity. The study mentioned that the hydrogels are still frost-resistant at -17°C, but long-term exposure to extreme low temperatures may affect their performance.
[0005] In summary, finding new methods or introducing new component structures to improve the adhesion, anti-drying and anti-freezing properties of ion-conductive composite hydrogels and to endow them with mechanical, temperature and humidity sensing properties without greatly affecting their properties is particularly important for the multifunctionalization of hydrogel sensors. Summary of the invention
[0006] The purpose of the present invention includes providing a simple and effective method for preparing a composite cross-linked ion conductive hydrogel, which can improve the mechanical properties, adhesion properties and anti-drying and anti-freezing properties of the hydrogel, and can be used for the assembly application of resistive flexible stress strain, temperature and humidity sensors.
[0007] The embodiment of the present invention can be implemented as follows: In a first aspect, an embodiment of the present invention provides a method for preparing an adhesion-modified composite ion-conductive hydrogel that can be used for temperature and humidity sensing, comprising: Add polyvinyl alcohol to deionized water, heat to above 80°C and stir to form a PVA solution; The cellulose is dissolved in a sodium hydroxide / urea aqueous solution, and monomer allyl glycidyl ether is added, and the mixture is reacted at room temperature and then dialyzed to obtain a cellulose solution; After adding the cellulose solution to the PVA solution, acrylamide, acrylic acid, deionized water, polyol and lithium / potassium salt of the conductive phase are added, and the mixture is stirred evenly at 40° C. to 50° C. for 10 to 20 minutes to obtain a uniform precursor solution; then a covalent crosslinking agent and a water-soluble initiator are added in sequence, and after stirring evenly, the mixture is placed in a mold and sealed; After heating the reaction at 50-60°C for 4-6 hours, a hydrogel precursor based on covalently cross-linked polyacrylamide is obtained; The precursor is frozen at low temperature and then restored to room temperature to obtain a covalent-physical composite cross-linked hydrogel.
[0008] The hydrogel is cut into a size that is convenient for assembly and then placed in a lithium salt solution with polyol / water as a solvent for a second time to perform solution exchange at 35-45° C. for 12-24 hours to obtain an ion conductive hydrogel.
[0009] Further, in an optional embodiment, polyvinyl alcohol (PVA) is added to deionized water, heated and stirred to form a PVA solution, the concentration of the PVA solution is 10-15wt%, and the temperature is raised to 90°C and stirred for 1-2 hours.
[0010] Furthermore, in an optional embodiment, the cellulose solution is prepared by mixing cellulose powder with an aqueous solution of sodium hydroxide / urea, wherein the concentration ratio of cellulose, NaOH and urea is 4%:7%:12%, stirring to a uniform suspension and freezing at -20°C for 12 h, followed by thawing at room temperature for 4-6 hours and stirring and shearing at 600 rpm for 10-20 min to obtain a cellulose precursor solution.
[0011] Furthermore, allyl glycidyl ether is added to the above-mentioned cellulose precursor at room temperature and stirred for sufficient reaction for 6-8 hours, and then transferred to a dialysis bag and dialyzed in deionized water until neutral to obtain a nanocellulose solution; wherein the molar ratio of the added amount of allyl glycidyl ether to the cellulose glucose unit in the solution is 1.5.
[0012] Furthermore, the first in-situ addition of the polyol is used to modify the solvent environment of the reaction process, and the selected polyol is glycerol or ethylene glycol, and the volume fraction is 10-15% of the total precursor solution.
[0013] Furthermore, the mass ratio of acrylamide to acrylic acid in the in-situ copolymerization system is 9:1-7:3; the mass ratio of the copolymerization system, polyvinyl alcohol, and cellulose is 10:2-4:0.5-0.8.
[0014] Further, in an optional embodiment, the chemical crosslinking agent is N,N'-methylenebisacrylamide, and the content of the chemical crosslinking agent is 0.1% to 0.5% of the total mass of the acrylamide and acrylic acid.
[0015] Furthermore, in an optional embodiment, the water-soluble initiator is ammonium persulfate or potassium persulfate, and its content is 0.2% to 0.8% of the total mass of the acrylamide and acrylic acid.
[0016] Furthermore, in an optional embodiment, in the step of adding the cellulose solution to a PVA solution, and then adding deionized water, polyol, acrylamide, acrylic acid, and lithium / potassium salt, and mixing and stirring to obtain a uniform solution, the total mass fraction of matrix solutes such as acrylamide, acrylic acid, and polyvinyl alcohol is 15%~20%, and the concentration of lithium / potassium salt is 0.5~1 mol / L.
[0017] Furthermore, in an optional embodiment, the hydrogel precursor is frozen at a low temperature and then returned to room temperature. The freezing temperature is -25 to -35°C, the freezing time is 12 hours, and the time for returning to room temperature is 4 to 6 hours; the number of cycles is 1 to 2 times.
[0018] Furthermore, in the water / polyol solution used in the secondary solution exchange, the type of polyol is ethylene glycol or propylene glycol, and the volume fraction is 50-75%.
[0019] Furthermore, in the water / polyol solution used in the secondary solution exchange, the salt serving as the conductive phase is LiCl or KCl, with a molar fraction of 1 to 2 mol / L.
[0020] Furthermore, the amount of water / polyol solution used in the secondary solution exchange is not less than 500% of the initial volume of the hydrogel; the solution exchange temperature is 35-45° C., and the exchange time is 12-24 hours.
[0021] The method for preparing the durable and adhesion-modified composite cross-linked ion-conductive hydrogel provided by the present invention has the following beneficial effects: Based on the composite cross-linked ion conductive hydrogel prepared by the prior art, the present application adopts a step-by-step introduction method of in-situ + non-in-situ exchange of solvent phase and conductive phase: first, the reaction is carried out under the conditions of low polyol solvent concentration and low conductive phase ion concentration, and the partial solvent exchange process is first integrated into the one-pot reaction of the hydrogel substrate, in which cellulose is grafted onto the polyacrylamide / polyacrylic acid copolymer molecular chain in situ and a reversible polyvinyl alcohol physical cross-linking network is introduced to form a covalent-physical composite cross-linking structure; under the conditions of high vapor pressure polyol / water as solvent, the in-situ reaction time is slightly extended, the temperature of the freeze-thaw cycle is reduced, and the number of cycles is reduced, while introducing free ions of part of the conductive phase. The precursor prepared subsequently undergoes secondary solvent exchange under the conditions of high polyol concentration and regulated ion concentration, so that it can rapidly increase the polyol concentration inside the hydrogel at a higher temperature and in a shorter time and rapidly adjust the ion concentration through osmosis, so that the hydrogel can achieve more sufficient solution exchange in the case of block. The prepared hydrogel has a tensile strength of up to 0.9272MPa, an elongation at break of more than 450%, a self-adhesion energy of up to 17.64 J / m2, and good electrical conductivity. It can be used to assemble into stress-strain, temperature and humidity sensors to monitor human activity, respiration, skin temperature and ambient humidity. Its durability has been improved and it has the ability to resist low temperatures and dryness.
[0022] In a second aspect, an embodiment of the present invention provides an adhesive, durable modified composite cross-linked ion conductive hydrogel that can be used for mechanical, temperature and humidity sensing, and is manufactured using any of the aforementioned preparation methods.
[0023] In a third aspect, an embodiment of the present invention provides an adhesion-modified ion-conductive hydrogel storage device that can be used for temperature and humidity sensing.
[0024] The present invention discloses an adhesion-modified ion conductive hydrogel storage device that can be used for temperature and humidity sensing, comprising a storage box, a temperature and humidity sensor fixedly installed inside the storage box, a sealing cover fixedly installed on the top of the storage box, an air pressure regulating valve arranged on the sealing cover, a support frame fixedly installed inside the storage box, a plurality of hydrogel fixing grooves fixedly installed on the support frame, an adhesion layer arranged inside the hydrogel fixing groove, the adhesion layer being composited by polydopamine and polyacrylamide, a humidifier fixedly installed inside the storage box, the humidifier being connected to the inside of the storage box through a pipeline, a heater fixedly installed inside the storage box, the heater being connected to the temperature and humidity sensor through a wire, a cooling device fixedly installed at the bottom of the storage box, the cooling device being connected to the inside of the storage box through a pipeline, a controller fixedly installed inside the storage box, the controller being electrically connected to the temperature and humidity sensor, the humidifier, the heater and the cooling device.
[0025] A sealing ring is provided between the sealing cover and the storage box, and the sealing ring is used to prevent outside air from entering the storage box. A filter is provided inside the humidifier, and the filter is used to filter impurities in water vapor. A temperature control module is provided inside the heater, and the temperature control module is used to accurately control the output temperature of the heater. A refrigerant circulation system is provided inside the cooling device, and the refrigerant circulation system is used to improve cooling efficiency.
[0026] Through the set adhesion layer, the mixed material of polydopamine and polyvinyl alcohol can enhance the adhesion between the hydrogel and the hydrogel fixing groove, preventing the hydrogel from sliding or falling off during storage. The temperature and humidity sensor monitors the temperature and humidity inside the storage box in real time and transmits the data to the controller. The controller adjusts the working state of the heater and the cooling device according to the data to maintain the appropriate temperature inside the storage box. The temperature and humidity sensor adjusts the humidity inside the storage box by controlling the inflow of external water source to prevent the hydrogel from losing water in a dry environment. The air pressure regulating valve can adjust the air pressure inside the storage box to prevent the hydrogel from deforming under high pressure environment.
[0027] The temperature and humidity sensor monitors the temperature and humidity inside the storage box in real time, and transmits the monitored data to the controller. The controller adjusts the working state of the heater and the cooling device according to these data to maintain the appropriate temperature inside the storage box. When the temperature inside the storage box is too high or too low, the controller will automatically adjust the working state of the heater and the cooling device to ensure that the temperature inside the storage box is always kept within the appropriate range. A temperature control module is provided inside the heater, and the temperature control module is used to accurately control the output temperature of the heater. A refrigerant circulation system is provided inside the cooling device, and the refrigerant circulation system is used to improve the cooling efficiency.
[0028] The temperature and humidity sensor adjusts the humidity inside the storage box by controlling the inflow of external water source. The controller is connected to the external water source. When the humidity inside the storage box is lower than the set value, the controller will automatically turn on and add the filtered water vapor into the storage box through the filter inside the humidifier to adjust the humidity to a suitable level. This can effectively prevent the hydrogel from losing water in a dry environment and maintain the performance and stability of the hydrogel.
[0029] The air pressure regulating valve on the sealing cover can adjust the air pressure inside the storage box to prevent the hydrogel from deforming under high pressure. When the air pressure inside the storage box is too high or too low, the air pressure regulating valve will automatically adjust to ensure that the air pressure inside the storage box is always kept within an appropriate range, avoiding adverse effects on the hydrogel due to changes in air pressure.
[0030] The present invention discloses an adhesion-modified ion-conductive hydrogel storage device that can be used for temperature and humidity sensing. Through the provided adhesion layer, the mixed material of polydopamine and polyvinyl alcohol can enhance the adhesion between the hydrogel and the partition plate, thereby preventing the hydrogel from sliding or falling off during storage. The temperature and humidity sensor monitors the temperature and humidity inside the storage box in real time, and transmits the data to the controller, which adjusts the working state of the heating plate and the cooling device according to the data to maintain a suitable temperature inside the storage box. The humidity regulator adjusts the humidity inside the storage box by controlling the inflow of the external water source, thereby preventing the hydrogel from losing water in a dry environment. The air pressure regulating valve can adjust the air pressure inside the storage box to prevent the hydrogel from deforming under high pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings: Figure 1 1 is the tensile stress-strain curve of each embodiment and comparative example; Figure 2 This is the resistance change curve of Example 1 when stretched 300 times with a strain of 50%; Figure 3 is the self-adhesion energy of each embodiment and comparative example; Figure 4 is the self-adhesion image between one side of the block hydrogel and different materials in Example 4; Figure 5 The resistance retention rate of some embodiments and comparative examples varies with aging time during ventilation natural aging and the relative humidity of the environment during measurement; Figure 6 The resistance change curves of some embodiments and comparative examples during the freezing aging process at -20°C; Figure 7 are humidity-resistance cycle response curves of some embodiments; Figure 8 is the temperature-resistance response recovery curve of Example 3 at different temperatures; Fig. 9 The resistance change curve of Example 4 for monitoring the partial activities and skin temperature of the human body; Fig.10 is a three-dimensional diagram of an adhesion-modified ion-conductive hydrogel storage device that can be used for temperature and humidity sensing of the present invention; Fig.11 is a schematic diagram of the internal structure of the storage box in the present invention; Fig.12 It is a schematic diagram of the structure of the partition plate and the adhesion layer in the present invention.
[0032] In the figure: 1. Storage box; 2. Temperature and humidity sensor; 3. Sealing cover; 4. Air pressure regulating valve; 5. Partition plate; 6. Adhesion layer; 7. Heating plate; 8. Temperature controller; 9. Cooling device; 10. Refrigerant circulation system; 11. Humidity regulator; 12. External water source. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations. Unless otherwise specified in the following embodiments, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0034] Example 1 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; 4 g of cellulose powder was dissolved in 100 ml of aqueous solution containing 7 g of sodium hydroxide and 12 g of urea, stirred to form a uniform suspension, and then frozen at -20°C for 12 hours. After thawing at room temperature for 4 hours, stirred and sheared at 600 rpm for 10 minutes. Then, allyl glycidyl ether with a molar ratio of 1.5 to glucose units in cellulose was added, reacted at room temperature for 6 hours, and then dialyzed to neutrality to obtain system 2. 10 ml of system 2 solution was added to 50 ml of the above system 1 solution, and then 13.5 g of acrylamide, 1.5 g of acrylic acid, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water were added to control the total volume of the solution to 200 ml, and then mixed and stirred at 40°C for 10 minutes to obtain a uniform precursor solution system 3; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 4 was obtained and placed in a mold and sealed; After heating the system 4 in the mold at 50° C. for 5 hours, a composite cross-linked hydrogel precursor was obtained; The precursor was frozen at -30°C for 12 hours and then thawed at room temperature for 4 hours.
[0035] The precursor is then placed in an exchange solution of 1 mol / L LiCl / 50% volume fraction of glycerol, and the solution exchange is carried out at 35°C for 24 hours to obtain a modified composite cross-linked ion conductive hydrogel.
[0036] like Figure 1 As shown, the tensile strength of the prepared hydrogel is 0.9083 MPa and the elongation at break is 448.1%.
[0037] Example 2 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; 4 g of cellulose powder was dissolved in 100 ml of aqueous solution containing 7 g of sodium hydroxide and 12 g of urea, stirred to form a uniform suspension, and then frozen at -20°C for 12 hours. After thawing at room temperature for 4 hours, stirred and sheared at 600 rpm for 10 minutes. Then, allyl glycidyl ether with a molar ratio of 1.5 to glucose units in cellulose was added, reacted at room temperature for 6 hours, and then dialyzed to neutrality to obtain system 2. 20 ml of system 2 solution was added to 50 ml of the above system 1 solution, and then 13.5 g of acrylamide, 1.5 g of acrylic acid, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water were added to control the total volume of the solution to 200 ml, and then mixed and stirred at 40°C for 10 minutes to obtain a uniform precursor solution system 3; Then, 100 mg of initiator ammonium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 4 was obtained and placed in a mold and sealed; After the system 4 in the mold was heated at 50° C. for 5 hours, a hydrogel precursor based on covalently cross-linked polyacrylamide was obtained; The precursor was frozen at -30°C for 12 hours and then thawed at room temperature for 4 hours.
[0038] The precursor is then placed in an exchange solution of 1 mol / L LiCl / 50% volume fraction of glycerol, and the solution exchange is carried out at 35°C for 24 hours to obtain a modified composite cross-linked ion conductive hydrogel.
[0039] like Figure 1 As shown, the tensile strength of the prepared hydrogel is 0.8412 MPa and the elongation at break is 429.4%.
[0040] Example 3 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; 4 g of cellulose powder was dissolved in 100 ml of aqueous solution containing 7 g of sodium hydroxide and 12 g of urea, stirred to form a uniform suspension, and then frozen at -20°C for 12 hours. After thawing at room temperature for 4 hours, stirred and sheared at 600 rpm for 10 minutes. Then, allyl glycidyl ether with a molar ratio of 1.5 to glucose units in cellulose was added, reacted at room temperature for 6 hours, and then dialyzed to neutrality to obtain system 2. 10 ml of the system 2 solution was added to 50 ml of the above system 1 solution, and then 10.5 g of acrylamide, 4.5 g of acrylic acid, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water were added to control the total volume of the solution to 200 ml, and then mixed and stirred at 40°C for 10 minutes to obtain a uniform precursor solution system 3; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 4 was obtained and placed in a mold and sealed; After the system 4 in the mold was heated at 50° C. for 5 hours, a hydrogel precursor based on covalently cross-linked polyacrylamide was obtained; The precursor was frozen at -30°C for 12 hours and then thawed at room temperature for 4 hours.
[0041] The precursor is then placed in an exchange solution of 1 mol / L LiCl / 50% volume fraction of glycerol, and the solution exchange is carried out at 35°C for 24 hours to obtain a modified composite cross-linked ion conductive hydrogel.
[0042] like Figure 1 As shown, the prepared hydrogel has a tensile strength of 0.8173 MPa and an elongation at break of 425.4%.
[0043] Example 4 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; 4 g of cellulose powder was dissolved in 100 ml of aqueous solution containing 7 g of sodium hydroxide and 12 g of urea, stirred to form a uniform suspension, and then frozen at -20°C for 12 hours. After thawing at room temperature for 4 hours, stirred and sheared at 600 rpm for 10 minutes. Then, allyl glycidyl ether with a molar ratio of 1.5 to glucose units in cellulose was added, reacted at room temperature for 6 hours, and then dialyzed to neutrality to obtain system 2. Add 20 ml of system 2 solution to 50 ml of the above system 1 solution, then add 12 g of acrylamide, 3 g of acrylic acid, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water to control the total volume of the solution to 200 ml, then mix and stir evenly at 40°C for 10 minutes to obtain a uniform precursor solution system 3; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 4 was obtained and placed in a mold and sealed; After heating the system 4 in the mold at 50° C. for 5 hours, a composite cross-linked hydrogel precursor was obtained; The precursor is frozen at -30°C for 12 hours, and then placed at room temperature for 4 hours before melting to obtain a modified composite cross-linked ion conductive hydrogel.
[0044] like Figure 1 As shown, the tensile strength of the prepared hydrogel is 0.9272 MPa and the elongation at break is 466.5%.
[0045] Comparative Example 1 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; 4 g of cellulose powder was dissolved in 100 ml of aqueous solution containing 7 g of sodium hydroxide and 12 g of urea, stirred to form a uniform suspension, and then frozen at -20°C for 12 hours. After thawing at room temperature for 4 hours, stirred and sheared at 600 rpm for 10 minutes. Then, allyl glycidyl ether with a molar ratio of 1.5 to glucose units in cellulose was added, reacted at room temperature for 6 hours, and then dialyzed to neutrality to obtain system 2. 10 ml of system 2 solution was added to 50 ml of the above system 1 solution, and then 15 g of acrylamide, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water were added to control the total volume of the solution to 200 ml, and then mixed and stirred at 40°C for 10 minutes to obtain a uniform precursor solution system 3; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 4 was obtained and placed in a mold and sealed; After heating the system 4 in the mold at 50° C. for 5 hours, a composite cross-linked polyacrylamide / polyvinyl alcohol hydrogel precursor was obtained; The precursor is frozen at -30°C for 12 hours, and then placed at room temperature for 4 hours before melting to obtain a composite cross-linked ion conductive hydrogel.
[0046] like Figure 1 As shown, the prepared hydrogel has a tensile strength of 0.7827 MPa and an elongation at break of 376.5%.
[0047] Comparative Example 2 A method for preparing an adhesion and durability modified composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; Add 12 g of acrylamide, 3 g of acrylic acid, 4 g of lithium chloride, 25 ml of glycerol and an appropriate amount of deionized water to the system 1 solution to control the total volume of the solution to 200 ml, then mix and stir evenly at 40° C. for 10 minutes to obtain a uniform precursor solution system 2; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 3 was obtained and placed in a mold and sealed; After heating the system 3 in the mold at 50° C. for 5 hours, a polyacrylamide / polyacrylic acid / polyvinyl alcohol hydrogel precursor without cellulose grafting was obtained; The precursor is frozen at -30°C for 12 hours, and then placed at room temperature for 4 hours before melting to obtain a composite cross-linked ion conductive hydrogel.
[0048] like Figure 1 As shown, the prepared hydrogel has a tensile strength of 0.7551 MPa and an elongation at break of 402.3%.
[0049] Comparative Example 3 A method for preparing a composite cross-linked ion conductive hydrogel comprises the following steps: Add 10g of polyvinyl alcohol to 90ml of deionized water, heat to 90°C and stir for 1 hour, during which time continue to add appropriate amount of deionized water to offset the evaporated water to ensure that the total solution volume is 100ml, forming system 1; Add 12 g of acrylamide, 3 g of acrylic acid, 4 g of lithium chloride and an appropriate amount of deionized water to the system 1 solution to control the total volume of the solution to 200 ml, then mix and stir evenly at 40° C. for 10 minutes to obtain a uniform precursor solution system 2; Then, 100 mg of initiator potassium persulfate and 50 mg of covalent crosslinking agent N,N'-methylenebisacrylamide were added in sequence, and after stirring evenly, system 3 was obtained and placed in a mold and sealed; After heating the system 3 in the mold at 50°C for 5 hours, a covalently cross-linked hydrogel precursor was obtained; The precursor is frozen at -30°C for 12 hours, and then placed at room temperature for 4 hours before melting to obtain a composite cross-linked ion conductive hydrogel without polyol solvent and cellulose grafting.
[0050] like Figure 3 and Figure 5 , 6 As shown, Comparative Example 3 is almost unable to self-adhere and is difficult to maintain the original resistance in both freezing and natural aging tests.
[0051] The invention also provides an adhesion-modified ion-conductive hydrogel storage device that can be used for temperature and humidity sensing.
[0052] like Figures 10 to 12 As shown, an adhesion-modified ion conductive hydrogel storage device for temperature and humidity sensing described in an embodiment of the present invention includes a storage box 1, a temperature and humidity sensor 2 is fixedly installed inside the storage box 1, a sealing cover 3 is fixedly installed on the top of the storage box 1, and an air pressure regulating valve 4 is arranged on the sealing cover 3, a support frame 5 is fixedly installed inside the storage box 1, a plurality of hydrogel fixing grooves 6 are fixedly installed on the support frame 5, an adhesion layer 7 is arranged inside the hydrogel fixing groove 6, and the adhesion layer 7 is composited by polydopamine and polyacrylamide, a humidifier 8 is fixedly installed inside the storage box 1, and the humidifier 8 is connected to the inside of the storage box 1 through a pipe 12, a heater 9 is fixedly installed inside the storage box 1, and the heater 9 is connected to the temperature and humidity sensor 2 through a wire 13, a cooling device 10 is fixedly installed at the bottom of the storage box 1, and the cooling device 10 is connected to the inside of the storage box 1 through a pipe 12, and a controller 11 is fixedly installed inside the storage box 1, and the controller 11 is electrically connected to the temperature and humidity sensor 2, the humidifier 8, the heater 9 and the cooling device 10.
[0053] A sealing ring 14 is provided between the sealing cover 3 and the storage box 1, and the sealing ring 14 is used to prevent outside air from entering the storage box 1. A filter 15 is provided inside the humidifier 8, and the filter 15 is used to filter impurities in water vapor. A temperature control module 16 is provided inside the heater 9, and the temperature control module 16 is used to accurately control the output temperature of the heater 9. A refrigerant circulation system 17 is provided inside the cooling device 10, and the refrigerant circulation system 17 is used to improve cooling efficiency.
[0054] Through the provided adhesive layer 7, the mixed material of polydopamine and polyvinyl alcohol can enhance the adhesion between the hydrogel and the hydrogel fixing groove 6, thereby preventing the hydrogel from sliding or falling off during storage. The temperature and humidity sensor 2 monitors the temperature and humidity inside the storage box 1 in real time, and transmits the data to the controller, which adjusts the working state of the heater 9 and the cooling device 10 according to the data to maintain a suitable temperature inside the storage box 1. The temperature and humidity sensor 2 adjusts the humidity inside the storage box 1 by controlling the inflow of the external water source to prevent the hydrogel from losing water in a dry environment. The air pressure regulating valve 4 can adjust the air pressure inside the storage box 1 to prevent the hydrogel from deforming under high pressure.
[0055] In a specific embodiment, the adhesive modified ion conductive hydrogel storage device for temperature and humidity sensing of the present invention is first used to store the hydrogel. The adhesive modified ion conductive hydrogel to be stored is placed on the hydrogel fixing groove 6. The adhesive layer 7 on the hydrogel fixing groove 6 can effectively enhance the adhesion between the hydrogel and the hydrogel fixing groove 6, thereby preventing the hydrogel from sliding or falling off during storage. The adhesive layer 7 is made of a mixture of polydopamine and polyvinyl alcohol. This material combination can provide good adhesion performance and biocompatibility, and at the same time has a certain mechanical strength, thereby ensuring that the hydrogel will not fall off due to changes in the external environment during storage.
[0056] The temperature and humidity sensor 2 monitors the temperature and humidity inside the storage box 1 in real time, and transmits the monitored data to the controller. The controller adjusts the working state of the heater 9 and the cooling device 10 according to these data to maintain the appropriate temperature inside the storage box 1. When the temperature inside the storage box 1 is too high or too low, the controller will automatically adjust the working state of the heater 9 and the cooling device 10 to ensure that the temperature inside the storage box 1 is always kept within the appropriate range. A temperature control module 16 is provided inside the heater 9, and the temperature control module 16 is used to accurately control the output temperature of the heater 9. A refrigerant circulation system 17 is provided inside the cooling device 10, and the refrigerant circulation system 17 is used to improve the cooling efficiency.
[0057] The temperature and humidity sensor 2 adjusts the humidity inside the storage box 1 by controlling the inflow of the external water source. The controller 11 is connected to the external water source. When the humidity inside the storage box 1 is lower than the set value, the controller 11 will automatically turn on and add a proper amount of filtered water vapor into the storage box 1 through the filter 15 inside the humidifier 8 to adjust the humidity to a suitable level. This can effectively prevent the hydrogel from losing water in a dry environment and maintain the performance and stability of the hydrogel.
[0058] The air pressure regulating valve 4 provided on the sealing cover 3 can adjust the air pressure inside the storage box 1 to prevent the hydrogel from deforming under high pressure. When the air pressure inside the storage box 1 is too high or too low, the air pressure regulating valve 4 will automatically adjust to ensure that the air pressure inside the storage box 1 is always kept within an appropriate range, thereby preventing the hydrogel from being adversely affected by the air pressure change.
[0059] In the specific operation process, the adhesive modified ion conductive hydrogel to be stored is first placed on the hydrogel fixing groove 6 to ensure that the hydrogel is in full contact with the adhesive layer 7. Then the sealing cover 3 is closed, and the air pressure inside the storage box 1 is adjusted to a suitable level through the air pressure regulating valve 4. The temperature and humidity sensor 2 monitors the temperature and humidity inside the storage box 1 in real time and transmits the data to the controller. The controller adjusts the working state of the heater 9 and the cooling device 10 according to these data to maintain a suitable temperature inside the storage box 1. When the temperature inside the storage box 1 is too high or too low, the controller will automatically adjust the working state of the heater 9 and the cooling device 10 to ensure that the temperature inside the storage box 1 is always kept within a suitable range. The temperature and humidity sensor 2 adjusts the humidity inside the storage box 1 by controlling the inflow of the external water source to ensure that the hydrogel does not lose water due to drying.
[0060] Through the above specific implementation, the adhesive modified ion conductive hydrogel storage device for temperature and humidity sensing of the present invention can effectively solve the problems of insufficient adhesion, limited anti-drying performance and insufficient antifreeze performance of the adhesive modified ion conductive hydrogel during storage. The storage device can provide a stable and suitable storage environment by setting the adhesive layer, temperature and humidity sensor, heating plate, cooling device, humidity regulator and air pressure regulating valve to ensure the performance and stability of the hydrogel during storage.
[0061] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different terms to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in the functions of components as the criteria for distinction. For example, "including" mentioned throughout the specification and claims is an open term, so it should be interpreted as "including but not limited to". "Approximately" means that within an acceptable error range, those skilled in the art can solve technical problems within a certain error range and basically achieve technical effects.
[0062] It should be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.
[0063] The above description shows and describes several preferred embodiments of the present invention, but as mentioned above, it should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the invention concept described herein through the above teachings or the technology or knowledge of the relevant field. Changes and variations made by those skilled in the art do not depart from the spirit and scope of the present invention, and should be within the scope of protection of the claims attached to the present invention.
Claims
1. An adhesion-modified ion-conductive hydrogel for temperature and humidity sensing, characterized in that: Its components include: 10-15 parts of polyvinyl alcohol, 0.5-0.8 parts of cellulose, 9-13.5 parts of acrylamide, 1.5-4.5 parts of acrylic acid, 0.5-1 mol / L of lithium / potassium salt, 10-15 parts of polyol, 0.1-0.5 parts of covalent crosslinking agent, and 0.2-0.8 parts of water-soluble initiator.
2. The adhesion-modified ion-conductive hydrogel according to claim 1, characterized in that: The cellulose solution is prepared by mixing cellulose powder in an aqueous solution of sodium hydroxide / urea, wherein the concentration ratio of cellulose, sodium hydroxide and urea is 4%:7%:12%, stirring to a uniform suspension, freezing at -20°C for 12 hours, then thawing at room temperature for 4-6 hours, and then stirring and shearing at 600 rpm for 10-20 minutes to obtain a cellulose precursor solution; the cellulose precursor solution is reacted with allyl glycidyl ether at room temperature for 6-8 hours, and then transferred to a dialysis bag and dialyzed in deionized water until neutral to obtain a nanocellulose solution; wherein the molar ratio of the amount of allyl glycidyl ether added to the cellulose glucose unit in the solution is 1.
5.
3. The adhesion-modified ion-conductive hydrogel according to claim 1, characterized in that: The polyol is glycerol or ethylene glycol, and the volume fraction is 10-15% of the total precursor solution.
4. The adhesion-modified ion-conductive hydrogel according to claim 1, characterized in that: The covalent crosslinking agent is N,N'-methylenebisacrylamide, and its content is 0.1% to 0.5% of the total mass of acrylamide and acrylic acid; the water-soluble initiator is ammonium persulfate or potassium persulfate, and its content is 0.2% to 0.8% of the total mass of acrylamide and acrylic acid.
5. A method for preparing the adhesion-modified ion-conductive hydrogel according to any one of claims 1 to 6, characterized in that: The following steps are involved: Add polyvinyl alcohol to deionized water, heat to above 80°C and stir to form a PVA solution; The cellulose is dissolved in a sodium hydroxide / urea aqueous solution, and the monomer allyl glycidyl ether is added, reacted at room temperature, and then dialyzed to obtain a cellulose solution; After adding the cellulose solution to the PVA solution, acrylamide, acrylic acid, deionized water, polyol and lithium / potassium salt of the conductive phase are added, and the mixture is stirred evenly at 40-50° C. for 10-20 minutes to obtain a uniform precursor solution; then a covalent crosslinking agent and a water-soluble initiator are added in sequence, and after stirring evenly, the mixture is placed in a mold and sealed; After heating the reaction at 50-60°C for 4-6 hours, a hydrogel precursor based on covalently cross-linked polyacrylamide is obtained; The precursor is placed at a low temperature and frozen, and then returned to room temperature to obtain a covalent-physical composite cross-linked hydrogel; The hydrogel is cut into a size that is convenient for assembly and then placed in a lithium salt solution with polyol / water as a solvent for a second time to perform solution exchange at 35-45° C. for 12-24 hours to obtain an ion conductive hydrogel.
6. The preparation method according to claim 5, characterized in that: The precursor is frozen at a low temperature and then returned to room temperature, the freezing temperature is -25 to -35°C, the freezing time is 12 hours, and the time for returning to room temperature is 4 to 6 hours; the number of cycles is 1 to 2 times.
7. The preparation method according to claim 5, characterized in that: The concentration of the PVA solution is 10-15wt%, and the temperature is raised to 90°C and stirred for 1-2 hours; in the water / polyol solution used in the secondary solution exchange, the polyol type is ethylene glycol or propylene glycol, and the volume fraction is 50-75%; the salt used as the conductive phase is LiCl or KCl, and the molar fraction is 1-2 mol / L; the amount of solution used is not less than 500% of the initial volume of the hydrogel; the solution exchange temperature is 35-45°C, and the exchange time is 12-24 hours.
8. An adhesion-modified ion-conductive hydrogel storage device for temperature and humidity sensing, characterized in that: The invention comprises a storage box (1), wherein a temperature and humidity sensor (2) is fixedly installed inside the storage box (1), a sealing cover (3) is fixedly installed on the top of the storage box (1), and a gas pressure regulating valve (4) is arranged on the sealing cover (3), a support frame (5) is fixedly installed inside the storage box (1), and a plurality of hydrogel fixing grooves (6) are fixedly installed on the support frame (5), and an adhesive layer (7) is arranged inside the hydrogel fixing groove (6), and the adhesive layer (7) is composited with polydopamine and polyacrylamide, and a humidifier (8) is fixedly installed inside the storage box (1), and the humidifier (8) is connected to the interior of the storage box (1) through a pipe (12); a heater (9) is fixedly installed inside the storage box (1); the heater (9) is connected to the temperature and humidity sensor (2) through a wire (13); a cooling device (10) is fixedly installed at the bottom of the storage box (1); the cooling device (10) is connected to the interior of the storage box (1) through a pipe (12); a controller (11) is fixedly installed inside the storage box (1); the controller (11) is electrically connected to the temperature and humidity sensor (2), the humidifier (8), the heater (9) and the cooling device (10).
9. The adhesion-modified ion-conductive hydrogel storage device for temperature and humidity sensing according to claim 8, characterized in that: A sealing ring (14) is provided between the sealing cover (3) and the storage box (1), and the sealing ring (14) is used to prevent outside air from entering the interior of the storage box (1); a filter screen (15) is provided inside the humidifier (8), and the filter screen (15) is used to filter impurities in water vapor.
10. The adhesion-modified ion-conductive hydrogel storage device for temperature and humidity sensing according to claim 8, characterized in that: The heater (9) is provided with a temperature control module (16) therein, and the temperature control module (16) is used to accurately control the output temperature of the heater (9); the cooling device (10) is provided with a refrigerant circulation system (17) therein, and the refrigerant circulation system (17) is used to improve cooling efficiency.
Citation Information
Cited By
Super-tough polyvinyl alcohol composite hydrogel with biological activity and preparation method of super-tough polyvinyl alcohol composite hydrogel
CN121081726A